Cost Allocation for Capital Budgeting Decisions - Baldenius, Tim; Dutta, Sunil; Reichelstein, Stefan (The Accounting Review, 2007)
Investment decisions frequently require coordination across multiple divisions of a firm. This paper explores a class of capital budgeting mechanisms in which the divisions issue reports regarding the anticipated profitability of proposed projects. To hold the divisions accountable for their reports, the central office ties the project acceptance decision to a system of cost allocations comprised of depreciation and capital charges. If the proposed project concerns a common asset that benefits multiple divisions, then our analysis derives a sharing rule for dividing the asset among the users. Capital charges are based on a hurdle rate determined by the divisional reports. We find that this hurdle rate deviates from the firm's cost of capital in a manner that depends crucially on whether the coordination problem is one of implementing a common asset or choosing among multiple competing projects. We also find that more severe divisional agency problems will increase the hurdle rate for common assets, yet this is generally not true for competing projects.